Miocene magmatism and tectonics of the easternmost sector of the Calama-Olacapato-El Toro fault system in Central Andes at ∼24°S: Insights into the evolution of the Eastern Cordillera - Mazzuoli, R. (2008)
The Miocene Las Burras - Almagro - El Toro magmatic complex lies ∼300 km to the east of the Central Andes volcanic arc, in the easternmost sector of the transverse Calama - Olacapato - El Toro fault zone. The magmatic rocks of the Las Burras - Almagro - El Toro complex comprise a monzogabbro to monzogranite laccolith like intrusion and basaltic andesite to dacite volcanic rocks that include sevenlithostratigraphic members. New Rb-Sr dates indicate that the intrusive rocks are ca. 14 Ma, and K-Ar dates suggest emplacement ages of ca. 12.8-6.4 Ma for the volcanic rocks. The emplacement of the intrusion was controlled by N-S - striking strike-slip faults in a context of oblique convergence; the volcanism, which occurred along WNW-ESE - and N-S - striking extensional faults, relates to the Calama - Olacapato - El Toro fault zone. Two magmatic phases were recognized. Intrusive and volcanic rocks of the older magmatic phase (ca. 14-13 Ma) are characterized by Ba/Nb (7-14), La/Ta (11-18), and isotopic ratios (87Sr/86Sr: 0.704339-0.705281, 143Nd/144Nd: 0.512713-0.512598), which are intraplate characteristics. The source of the older magmas was isotopically depleted lithospheric mantle rich in K, Rb, and Th. Energy constrained-assimilation and fractional crystallization (EC-AFC) modeling indicates that fractional crystallization and crustal assimilation moderately modified magma composition during its residence in the crust. The products of the younger magmatic phase (ca. 11-6 Ma) have higher Ba/Nb (24-42) and La/Ta (24-30) and 87Sr/86Sr (0.706738-0.708729) and lower 143Nd/144Nd (0.512433-0.512360). The results of EC-AFC modeling exclude a significant role for the upper crust in the generation of the most primitive magmas of this phase. Their compositions can be explained by (1) contamination of the primary magmas having originated in a depleted mantle with a mafic crust, or (2) the contribution of isotopically enriched mantle zones. Shallow differentiation and moderate contamination by continental crust can explain the composition of the intermediate and evolved products of the younger phase. The variation of the magma source characteristics at 11 Ma is discussed in the frame of the complex geo-dynamical setting in this region.